Plant Essential Oil with Biological Activity - Elshafie, Hazem Salaheldin; De Martino, Laura; Sofo, Adriano (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Plant essential oils (PEOs) are hydrophobic liquids that contain volatile chemical components that are derived from various plant parts. They are among the most important plant natural products because of their diverse biological features as well as their therapeutic and nutritional applications. In addition, several aromatic PEOs are used to flavor food and add aromas to incense in the culinary sector. Recently, many PEOs have demonstrated promising antimicrobial activity against different post-harvest diseases and have been considered as possible natural alternatives for chemical treatments. This Special Issue titled "Plant Essential Oil with Biological Activity" provided an overview of several elements of PEOs, including their biological applications, antimicrobial activities, bio-pharmaceutical properties, principal single constituents, and mechanisms of action. This Special Issues fills in knowledge gaps and aids in the advancement of EO applications around the world. This issue contains thirteen research articles and two review papers that address a wide range of topics and applications relevant to the bioactivity of PEOs.